Influence of Contextual Teaching and Learning Model on Elementary School Students’ Critical Thinking Ability - Yonanda, Devi Afriyuni; Patimah, Titin Siti; Efastri, Sean Marta; Vioreza, Niken (PUSAKA: Journal of Educational Review, 2025)
This research aims to determine the influence of the Contextual Teaching and Learning model on elementary school students' critical thinking abilities. The research method used was quasi-experimental using a nonequivalent control group design. The samples in this research were class IVC students and class IVB students at SDN Cicenang I for the 2024/2025 academic year with research subjects of 40 students who were determined through purposive sampling. The data collection technique in this research was through a critical thinking ability test in the form of an essay with 9 questions. This research uses quantitative data analysis techniques on post-test data. The analysis results show a significant difference in critical thinking abilities between students who studied using the Contextual Teaching and Learning model and those who learned using the Direct Instruction model. Based on hypothesis testing using the independent sample t-test, the sig (2-tailed) value was 0.022 < 0.05. So, it can be concluded that using the Contextual Teaching and Learning model influences the critical thinking abilities of class IV students at SDN Cicenang I.